Senior design project: galaxy clamp bike rack - Nakasone, Jayse, author; Roberts, Bonnie, advisor; Knaus, Pamela Vaughn, committee member (Colorado State University. Libraries, 2026)
Cycling is popular worldwide for recreation and transportation. Bike racks, especially those mounted on personal vehicles, allow people to take their bikes farther for recreation. However, the bike racks currently on the market skimp on securing the rear tire, relying only on a flexible plastic ratcheting strap, which is vulnerable to theft targeting the rear wheel. A survey conducted by our team confirms that many cyclists are uncomfortable leaving their bikes unattended on these vehicle-mounted bike racks. Our senior design team’s goal is to improve durability and integrate a locking mechanism into the rear part of a bike rack. Our project sponsor, a patent attorney based in Colorado, intends to patent our design and then approach established bike rack manufacturers such as Thule, Yakima, and Küat. He plans to offer licenses for the patented design, enabling manufacturers to legally incorporate our innovation into their future products. Using the engineering design process, our four-person team clarified sponsor requirements, researched the market, and established design objectives. We adapted our design to an up-to-date hitch-mounted bike rack from Thule. After brainstorming alternatives to the flexible strap, the team decided on a handcuff-inspired design and iterated through CAD models and low-cost rapid prototyping. To create a more production-ready prototype, our team decided to laser-cut steel parts and outsource the plastic parts to be manufactured via SLS 3D printing. Finally, we tested our design by fitting multiple bike types that the team owned and applying a vertical pulling force on the mechanism. Our bike rack with the redesigned rear mechanism met most of our design requirements. The final prototype was able to withstand a vertical pulling force of 150 pounds, exceeding our target of 100 pounds. The bike rack continues to accommodate road and mountain bikes. An improved vehicle-mounted bike rack encourages more people to use their bikes for commuting or recreational purposes. Studies have shown that bicycles have health and environmental benefits. Cycling produces zero tailpipe emissions, which reduces pollution in cities and lowers greenhouse gases in the atmosphere that contribute to climate change.
Keywords: mechanical engineering; senior design project; engineering